Clinical characteristics and cardiovascular risk profile in children and adolescents with latent autoimmune diabetes: Results from the German/Austrian prospective diabetes follow‐up registry. Issue 8 (27th November 2022) - Welters, Alena; Tittel, Sascha R.; Reinehr, Thomas; Weghuber, Daniel; Wiegand, Susanna; Karges, Wolfram; Freiberg, Clemens; Meissner, Thomas; Schloot, Nanette C.; Holl, Reinhard W.
Abstract: Aims: To characterize children and adolescents with latent autoimmune diabetes of the young (LADY), and to assess the utility of classifying individuals as LADYs regarding their cardiovascular (CV) risk factors. Methods: Data from 25, 520 individuals (age at diagnosis <18 years) of the Prospective Diabetes Follow‐up Registry Diabetes‐Patienten Verlaufsdokumentation (DPV) were analyzed. LADY was defined as positivity of ≥one islet autoantibody (iAb+) and an insulin‐free interval of ≥6 months upon diabetes diagnosis. LADYs were compared to iAb+ individuals immediately requiring insulin ("immunologically confirmed" type 1 diabetes, T1DM), iAb−/Ins− individuals ("classical" T2DM) and to those clinically defined as T2DM (iAbs not measured). Results: Clinical characteristics of LADYs ( n = 299) fell in between those with T1DM ( n = 24, 932) and T2DM (iAb−/Ins−, n = 152) or suspected T2DM (iAB not measured, n = 137). Stratifying LADYs according to their clinical diagnosis however revealed two distinct populations, highly resembling either T1DM or T2DM. Particularly, CV risk profile, precisely prevalence rates of arterial hypertension and dyslipidemia, was significantly higher in LADYs clinically classified as T2DM compared to LADYs classified as T1DM, and did not differ from those with "classical" T2DM. Conclusions: In terms of CV risk, classifying children and adolescents with diabetes as LADYs provides no additional benefit. Instead, clinical diagnosis seems to better assign individuals to appropriate risk groups for increased CV risk profiles.